EXPERIMENTAL DETERMINATION OF THE RESISTANCE COEFFICIENTS OF THE DUST-CLEANING DEVICE IN THE SOLUTION METHOD (American Journal of Pedagogical and Educational Research, 2025)
In this article, the values of the resistance coefficients of the contact elements of the local and three different sizes and the liquid droplet trap in the absence of liquid are determined for a device with a conical contact element for wet cleaning of dusty gases. Determined experimentally. As a result of this, liquid is supplied to the device, and the determination of resistance coefficients, total hydraulic resistance and construction. It is possible to determine and analyse fluid consumption and energy consumption to determine optimal cleaning efficiency values.